Uma discussão sobre o conhecimento matemático disseminado pelo PROFMAT para o ensino de funções à luz do MTSK - Valim, Jaqueline Lazaroto (2020)
This research aims to discuss the nature of the knowledge conveyed by the Professional Master's Program in Network Mathematics - PROFMAT, which constitutes itself as a public policy for teacher training, through a qualitative analysis of the textbook that guides one of the main subjects of the program, the “Real Numbers and Functions”. Such analysis focused on the developed approach of the theme "Functions", more specifically, "Related Functions", and was carried out in the light of the theoretical-analytical model Mathematics Teacher’s Specialized Knowledge (MTSK). Thus, it was evident, through this work, that the knowledge on the topic functions disseminated in and by PROFMAT privileges only one of the knowledge considered by MTSK as essencials for the teacher who teaches mathematics, the domain Mathematical Knowledge - MK, more specifically in regarding the subdomains Knowledge of Topics - Kot and Knowledge of Practices in Mathematics - KSM, that is, the teacher's specific knowledge for teaching content, which constitute a necessary basis for effective teaching and which constitute the Pedagogical Content Knowledge domain - PCK ceases to be evidenced and contemplated satisfactorily in the approach developed by the author of the text book “Numbers and Real Functions”.